Geotechnical and structural behavior of the railroad track in large-scale apparatus - Queiroz, R. C. [UNESP]; Macari, E. J. (IOS Press, 2009)
This paper analyses the static and dynamic behavior of the railroad track model in laboratory. Measurements of stresses and strains on a large-scale railroad track apparatus were studied. The model includes: compacted soil, representing the final layers of platform, ballast layer, and ties (steel, wooden, and pre-stressed concrete). The soil and soil ballast interface were instrumented with pneumatic stress gauge. Settlement measurement device were positioned at the same levels as the load cells. Loads were applied by hydraulic actuators, statically and dynamically. After the prescribed number of load cycles, in pre-determined intervals, stresses and strains were measured. Observations indicate that stress and strain distributions, transmitted by wooden or steel ties, behave similarly. A more favorable behavior was observed with pre-stressed concrete mono block ties. Non-linear response was observed after a threshold numbers of cycles were surpassed, showing that the strain modulus increases with the numbers of cycles. © 2009 IOS Press.
Keywords: Railroad large scale apparatus; Railroad ties; Railroad track; Compacted soil; Geotechnical; Load cells; Load cycle; Non-linear response; Settlement measurement; Static and dynamic behaviors; Stress and strain distribution; Stress gauges; Structural behaviors; Threshold numbers; Elasticity; Geotechnical engineering; Rail laying; Railroad tracks; Soil mechanics; Soils; Strain; Structural design; Geologic models